GENETIC VARIATION OF HOUSEKEEPING GENES IN MULTIDRUG RESISTANT PSEUDOMONAS AERUGINOSA - Hassan, Baraa Adnan; Hamada, Yasir Hamad; Abdullah, Iman Tajer (PT. Antis International Publisher, 2024)
Background: Pseudomonas aeruginosa is a prominent opportunistic pathogen responsible for nosocomial infections, particularly among immunocompromised individuals. Specific Background: Its ability to develop multiple antibiotic resistance poses a significant clinical challenge, highlighting the need for a deeper understanding of its genetic diversity and virulence factors. Knowledge Gap: While previous studies have explored antibiotic resistance mechanisms, there is limited research on the genetic diversity of Pseudomonas aeruginosa isolates in specific geographic regions, such as Kirkuk. Aims: This study aimed to investigate the genetic diversity of Pseudomonas aeruginosa isolates from clinical samples obtained from Kirkuk Civil Hospitals, utilizing Multi-Locus Sequence Typing (MLST) for genetic analysis. Results: Fourteen P. aeruginosa isolates were confirmed through biochemical tests and the VITEK-2 system, with an alarming 85.71% (12/14) exhibiting antibiotic resistance. Molecular analysis revealed the presence of several housekeeping genes, although some genes did not amplify. Notably, two new serotypes (PS3:id:9797 and PS4:id:9796) were identified and added to the MLST database, along with three new genes registered in NCBI. Phylogenetic analysis indicated a divergent cluster among three isolates. Novelty: This research contributes new insights into the genetic diversity of Pseudomonas aeruginosa, identifying novel serotypes and genes, which are critical for understanding its epidemiology and resistance mechanisms. Implications: The findings underscore the importance of ongoing surveillance of Pseudomonas aeruginosa in clinical settings to inform treatment strategies and public health policies aimed at managing antibiotic resistance and improving patient outcomes.